2020
DOI: 10.1002/jbio.202000287
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial photobiomodulation but not long‐term omega‐3 intake reduces epileptiform discharges in rats with stroke‐induced epilepsy

Abstract: Epilepsy is a yet under-recognized consequence after a stroke and nearly 30% of cases are pharmacoresistant. There is an unmet need for therapeutic interventions during epileptogenesis for better long-term disease outcomes. Transcranial photo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…In addition, PBM reduced the apoptotic ratio of parvalbumin-labeled interneurons and alleviated the aberrant extent of parvalbumin-labeled unstained somata of principal cells in the hippocampus. Second, Vogel et al ( 29 ) observed that PBM reduces epileptiform discharges after a stroke ( 29 ). They showed that a 780 nm wavelength laser treatment for 2 months after induction of photothrombotic stroke reduced late epileptic electrographic seizures, as well as the number of spikes in the ipsilateral and contralateral cortices and in the ventral posteromedial thalamic nuclei.…”
Section: Studies Of Photobiomodulation In Epilepsy Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PBM reduced the apoptotic ratio of parvalbumin-labeled interneurons and alleviated the aberrant extent of parvalbumin-labeled unstained somata of principal cells in the hippocampus. Second, Vogel et al ( 29 ) observed that PBM reduces epileptiform discharges after a stroke ( 29 ). They showed that a 780 nm wavelength laser treatment for 2 months after induction of photothrombotic stroke reduced late epileptic electrographic seizures, as well as the number of spikes in the ipsilateral and contralateral cortices and in the ventral posteromedial thalamic nuclei.…”
Section: Studies Of Photobiomodulation In Epilepsy Modelsmentioning
confidence: 99%
“…Although these studies present interesting behavioral findings on PBM in epilepsy ( 28 , 29 ), evidence regarding mitochondrial functions is still lacking. This line of reasoning would be interesting since studies show that mitochondrial damage under various conditions is restored by PBM.…”
Section: Studies Of Photobiomodulation In Epilepsy Modelsmentioning
confidence: 99%
“… 7 Vogel et al. 8 further revealed that repetitive tPBM (780 nm) reduced epileptiform discharges in a rat model of stroke-induced epilepsy. Regarding neuroprotection, tPBM has shown effects in reducing neuroinflammatory cytokines, 7 , 9 which along with neuron-specific enolase (NSE) increased in the hippocampus after convulsive status epilepticus (CSE).…”
Section: Introductionmentioning
confidence: 96%
“…Transcranial photobiomodulation (tPBM) is the application of PBM transcranially and noninvasively. tPBM has been applied to dementia including Alzheimer's disease, 23 traumatic brain injury, 24 stroke, 25 epilepsy, 17,21,26,27 PTSD, 28 anxiety and depression. 29 Corresponding to the two main mechanisms (α-synnuclein aggregation and mitochondrial dysfunction or failure of mitochondrial biogenesis) and a potential therapeutic target (microglial activation) in the pathogenesis of PD, PBM has correlated therapeutic effects against them respectively.…”
Section: Introductionmentioning
confidence: 99%